Hygro-Thermo-Mechanical Responses of Balsa Wood Core Sandwich Composite Beam Exposed to Fire - Van, Luan Tran; Legrand, Vincent; Casari, Pascal; Sankaran, Revathy; Show, Pau Loke; Berenjian, Aydin; Lay, Chyi How (MDPI, 2020)
In this study, the hygro-thermo-mechanical responses of balsa core sandwich structured composite was investigated by using experimental, analytical and numerical results. These investigations were performed on two types of specimen conditions: dry and moisture saturation sandwich composite specimens that are composed of E-glass/polyester skins bonded to a balsa core. The wet specimens were immersed in distilled water at 40 °C until saturated with water. The both dry and wet sandwich composite specimens were heated by fire. The mass loss kinetic and the mechanical properties were investigated by using a cone calorimeter following the ISO 5660 standard and three-point bending mechanical test device. Experimental data show that the permeability and fire resistance of the sandwich structure are controlled by two composite skins. Obtained results allow us to understand the Hygro-Thermo-Mechanical Responses of the sandwich structured composite under application conditions. © 2019 by the authors.